Ūrmiḷā - Daḷāi, Abhimanyu, 1948- (Kaṭaka : Mā Śāradā Pablikeśan, 2006)
Based on Hindu mythological character, Ūrmilā, serialized earlier in Nirmalya, Oriya serial.
Novel.
In Oriya.
Keywords: Ūrmilā (Hindu mythology) -- Fiction; Ūrmilā (Hindu mythology); Fiction